2021
DOI: 10.1016/j.heliyon.2021.e05901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the wound healing activity of the crude extract of root bark of Brucea antidysentrica, the leaves of Dodonaea angustifolia and Rhamnus prinoides in mice

Abstract: Background: Wounds are major problems of developing countries that can be managed alternatively using traditional medicinal plants. Since majority of currently available drugs for wound management are expensive and pose problems such as allergy and drug resistance, it is pivotal for the world to have intensified inquiries on the claimed medicinal plants to come up with wound healing chemicals being affordable, effective and safe. Ethiopian traditional healers recruit a wide range of medicinal plants with wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…In vivo study in mice revealed that the hydroalcoholic extracts of the leaves of R. prinoides possess wound healing activity established by a significant rate of wound contraction and shorter epithelization period. In this study, ten percent of 80% methanol leaves extract showed significant wound contraction against the control and rate increased in significant level with number of days p < 0.05, p < 0.01, and p < 0.001 on days 2 to 4, 8 to 10 and 12 to14, respectively (Tessema et al, 2021). Biological activities of different parts of R. prinoides are summerized here below (Table 4).…”
Section: Wound Healing Activitymentioning
confidence: 67%
See 1 more Smart Citation
“…In vivo study in mice revealed that the hydroalcoholic extracts of the leaves of R. prinoides possess wound healing activity established by a significant rate of wound contraction and shorter epithelization period. In this study, ten percent of 80% methanol leaves extract showed significant wound contraction against the control and rate increased in significant level with number of days p < 0.05, p < 0.01, and p < 0.001 on days 2 to 4, 8 to 10 and 12 to14, respectively (Tessema et al, 2021). Biological activities of different parts of R. prinoides are summerized here below (Table 4).…”
Section: Wound Healing Activitymentioning
confidence: 67%
“…Biological activities of different parts of R. prinoides are summerized here below (Table 4). (Wall et al, 1988) Leaves Antibacterial (Chhabra & Uiso, 1991;Chhabra et al, 1984;Molla et al, 2016) Insecticide (Van Puyvelde et al, 1985) Root bark Cytotoxic (Koch et al, 2005) Leaves, roots, bark root Antimalarial (Muregi et al, 2007) Leaves Wound healing (Tessema et al, 2021)…”
Section: Wound Healing Activitymentioning
confidence: 99%
“…Wound refers to a cut or break in the continuity of the skin caused by injury or operation [ 1 , 2 ]. A wound is classified as an acute and chronic wound [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wounds associated with vascular insufficiency, diabetes mellitus (DM), and local-pressure effects are included in chronic wounds [ 5 , 6 ]. Based on different criteria; type of injury or presenting symptoms, clinical appearance, etiology, its depth, and location; wounds could be diabetic, cuts and bites, injuries, duodenal ulcers, and gastric [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation